Anesthesia in Obese Patients and Complications (IAHS Medical Journal, 2024)
Background: Almost all ages and socioeconomic categories are affected by the complex illness known as obesity, which has major social and psychological ramifications. Global obesity rates have reached epidemic proportions and obesity plays a significant role in the burden of chronic illnesses and disabilities worldwide. The aim of the study was to assess the Anesthesia in obese patient and its Complications in a tertiary care hospital.Materials and mathods: This cross-sectional observational study was carried out in the Department of Anesthesiology, Bangabandhu Memorial Hospital (BBMH) from July 2020 to June 2022.Total sample size was 200. Adult in-patients who had undergone non-cardiac surgery and were older than 18 with a BMI greater than 30 kg/m2 met the inclusion criteria. Pregnancy, ambulatory surgery and missing or insufficient data on the desired outcomes were the exclusion criteria.Results: Mean age ±SD was 32 ± 0.9 years. About 55% of the patients were female and 45% were male. Regarding ASA classification 53.5% had 2, 45.5% had 3 and 1.0% had 4 score. Regarding coexisting disease 42.5% had hypertension, 14% had dyslipidemia, 18% had DM type-2 and 7.5% had obstructive sleep apnea. Here, type of anesthesia was 55% general anesthesia, 6% normal mask ventilation, 25% regional anesthesia, 4% total intravenous anesthesia and 10% LMA (Laryngeal Mask Airway). Regarding complication 4.5% was Reintubation, 5.5 %Pneumonia, 7.5% Upper airway obstruction, 0.5% Delay emergence respectively. 2.5% Urinary retention, 5% Oliguria, 2% Wound infection. 0.5% myocardial infarction and 0.5% Cardiac arrest occurred and no death occur inpatient respectively.Conclusion: Obesity has long been seen from a surgical standpoint as a risk factor for unfavorable post-surgical outcomes. Patients who are morbidly obese may experience respiratory adverse effects following surgery as a result of physiological disruption. The undesirable effects range depending on the surgical population.IAHS Medical Journal Vol 7(1), June 2024; 97-101